2009
DOI: 10.1002/hep.22649
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the hedgehog pathway inhibits hepatoblastoma growth #

Abstract: Recent evidence has indicated that Hedgehog (Hh) signaling significantly contributes to liver development and regeneration and that activation of the pathway may contribute to growth of hepatocellular carcinoma (HCC) in adults. However, the role of Hh signaling in pediatric liver tumors remains to be elucidated. In this study, we show that Hh signaling is activated in hepatoblastoma (HB), the most common liver tumor in childhood, with most occurrences before the age of 3 years. The Hh target genes glioma-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 41 publications
4
79
0
Order By: Relevance
“…(28) It has been shown that blocking Gli1 inhibits heptoblastoma growth. (31) Cytotoxic therapies currently used for cancer treatment largely depend on activation of cancer cell apoptosis. Consequently, it is likely that IMD increases HCC cell growth by preventing tumor cells from undergoing apoptotic pathways through regulation of the Hedgehog pathway, which transcriptionally controls Bcl2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…(28) It has been shown that blocking Gli1 inhibits heptoblastoma growth. (31) Cytotoxic therapies currently used for cancer treatment largely depend on activation of cancer cell apoptosis. Consequently, it is likely that IMD increases HCC cell growth by preventing tumor cells from undergoing apoptotic pathways through regulation of the Hedgehog pathway, which transcriptionally controls Bcl2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction, complementary (c)DNA synthesis and quantitative polymerase chain reaction (qPCR) analysis were performed as previously described (26). Briefly, total RNA was isolated from all the samples using TRIzol ® reagent (Invitrogen Life Technologies, Carlsbad, CA, USA) and dissolved in RNase-free water.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, one study reported an overexpression of hedgehog members GLI1 and PTCH1 in tumors compared to normal liver tissues (54). More impressively, inhibiting this pathway with cyclopamine induced a striking growth inhibition of hepatoblastoma cells (54).…”
Section: Other Molecular Alterations Described In Hepatoblastomamentioning
confidence: 99%
“…In particular, one study reported an overexpression of hedgehog members GLI1 and PTCH1 in tumors compared to normal liver tissues (54). More impressively, inhibiting this pathway with cyclopamine induced a striking growth inhibition of hepatoblastoma cells (54). On the other hand, when analysing Notch signaling by immunohistochemistry, Litten et al revealed an overexpression of the NOTCH2 receptor in 92% of the tumors compared to normal liver tissues (55).…”
Section: Other Molecular Alterations Described In Hepatoblastomamentioning
confidence: 99%